“Moving Forward: Strengthening cooperation in Today’s Barents Region,” - Espiritu, Aileen Aseron (University of Lapland, 2015)
Source: http://www.barentsinfo.org/barentsstudies/English/Issues/2015-vol1-3 When the 1993 Kirkenes Declaration was ratified, the governments of Russia, Finland, Sweden, and Norway “expressed their conviction that expanded co-operation in the Barents Euro-Arctic Region (BEAR) will contribute substantially to stability and progress in the area and in Europe as a whole.” (Kirkenes Declaration 1993). Over 20 years later, and as we move forward, this goal is even more important and urgent as Europe and Russia find themselves on opposite sides of a geopolitical conflict in Russia’s southern borders with Ukraine. Economic sanctions employed by both sides have placed a significant halt to the trading and economic exchange between Russia and the rest of the Barents Region – the Northern municipalities of Norway, Finland, and Sweden. These have had significant impact on small and large communities that have relied on the economic, social, and cultural interrelationship across the Schengen-Russia border zones.